Memperluas Usaha Kuliner Nasi Padang di Negara Australia - Christian Joseph Silaban; Daniella Sitanggang; Vina Verensia Liandi; Keshia Annisa Putri; Yuliana Yuli W; Mulyadi M; Rerin Maulinda; R. Manalu; Suprima S (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
A typical Indonesian culinary dish, Nasi Padang, is increasingly popular in Australia. Dishes such as rendang, satay Padang, curry and rendang chips attract the interest of culinary connoisseurs in Australia. This certainly opens up great opportunities for Indonesian culinary delights, one of which is Nasi Padang, to become better known abroad. Our aim in conducting this research is to have a positive impact on the vision of a Golden Indonesia 2045. We focus on answering questions whose answers will hopefully help the development of Nasi Padang culinary expansion in Australia. In this research, we used information from various sources. We conducted interviews with sources, using information from trusted online sites and journals that discuss this topic. From the results of the research that has been carried out, we found several differences between Nasi Padang sold in Australia and Indonesia, starting in terms of price, taste and access to enjoying Nasi Padang. Apart from discussing the differences between the two, we also try to discuss several other things. We are trying to compile what things must be considered to expand the Nasi Padang business in Australia and explain several ways to increase sales of Nasi Padang there.